THE MORAL HARASSMENT IN HEALTH PROFESSIONALS IN AN ORGANIZATION PUBLIC - Daniel, Hélcia; Macêdo, Kátia Barbosa (IJRDO-Journal of Applied Science, 2015)
The text aims to discuss and present data on indicators of suffering and bullying in a public institution with group of professionals in healthcare. We used the theoretical and methodological approach of psychodynamic clinical work, which dealt with bullying in the emphasis the centrality of work seen in a psychic constitution important factor of the individual and subjective mobilization of this subject from their relationships at work. Bullying is abusive behavior, manifested in behavior, words and actions that may have negative effects on the psychological and physical. Thus, it analyzes the experiences of suffering caused by bullying a group of professionals, discussing its causes and consequences in the workplace. Guiding questions were prepared on the categories of psychodynamic and clinical work demonstrating the subjective mobilization and bullying as the central element of the study. As Results revealed the incidence of bullying at different levels of hierarchy and peer and its negative consequences, both in mental health, such as anxiety, anger, low esteem, as physical conditions such as illness, the removal of work, was noted aggravating psychological conditions in some participants, it was realized too, was the organization of work, required goals and results involving overload, pressure on results among others, greatly exacerbate the presence on condition of bullying in the group . Although as a result the lack of recognition was evident, and the condition of lack of speech and improvement actions by the agents causing discouragement and Negligence thereof.